Aspects of Latin American Spanish dialectology in honor of Terrell A. Morgan - Díaz-Campos, Manuel; Sessarego, Sandro; Morgan, Terrell A., 1957- (Issues in Hispanic and Lusophone linguistics ;, 2021)
"This book focuses on contemporary sociolinguistic approaches to Spanish dialectology. Each of the authors draws on key issues of contemporary sociolinguistics, combining theoretical approaches to empirical data collection. Overall, these chapters address topics concerning language variation and change, sound production and perception, contact linguistics, language teaching, language policy and ideologies. The authors urge us, as linguists, to take a stand on important issues, and to continue applying theory to praxis so as to advance the frontiers of research of the field. This edited volume in honor of Professor Terrell A. Morgan is a means of celebrating an amazing friend, advisor and human being, who has dedicated his career to teaching graduate and undergraduate students, performed key research in the field, and helped to further pedagogy in the classroom through his textbooks, seminars and websites"--